Determinants of Modern Contraceptive Use Among Married Women in Indonesia Urban (Jurnal Ilmu Kesehatan Masyarakat, 2022)
The use of contraceptives in Indonesia among married women has tended to be stagnant in the last 3 years. Indonesia's 2017 demographic and health survey report reports that the prevalence of modern contraceptive use was lower among women in urban areas (59%) than in rural areas (55%). This study aims to analyze the determinant of modern contraceptive use in married women in Indonesian urban. This study is a quantitative study with a cross-sectional design. We used secondary data from Indonesia Health and Demographics Survey 2017. The population of this study was married women. We got a sample was 15,520 respondents. We analyze the predictor of modern contraceptive use by using logistic regression. Respondents using modern contraceptives were 53.5%.  Age, education level, number of living children, number of ideal children, employment status, economic status, and region have a significant association with modern contraceptive use in Indonesian urban. The most dominant factor associated with modern contraceptive use is the number of living children >2 children. Proper dissemination of information on the use of modern contraceptives needs to be expanded to increase contraceptive use.